Distribution, transmission, and risk factors of infection with canine vector-borne pathogens in wild foxes and free-ranging dogs in Chile - Di Cataldo, Sophia (2022)
Canine vector-borne pathogens (CVBP) distribution tends to be circumscribed to certain areas with climatic features where their vectors are able to persist. In this aspect, Chile possesses a marked variety of bioclimates that provides an ideal scenario to study the distribution of vector-borne pathogens, considering that ticks of the Rhipicephalus sanguineus species group are widely distributed in the country. Despite this, information about the presence, distribution, and impact of CVBP in domestic and wild canines in Chile is very scarce. In this study, blood and serum samples of 981 dogs, 155 Andean foxes (Lycalopex culpaeus), and 90 grey foxes (L. griseus) were obtained from six different bioclimatic regions throughout Chile.